Upaya Mengatasi Kecemasan Peserta Didik Kelas IX dalam Menghadapi Ujian Sekolah Melalui Bimbingan Klasikal di SMP Negeri 1 Semarang - Setiawati, Palupi Dwi; Suhendri, Suhendri; Indraswati, Veronica (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2024)
The aim of this research is to overcome anxiety in facing final exams in class IX students at SMP Negeri 1 Semarang by providing classical guidance services. Based on existing phenomena in the field, the percentage of students' anxiety in class IX of SMP Negeri 1 Semarang is 3.34%, which is included in the very high category. This research uses the action research method. The selected population was class IX students at SMP Negeri 1 Semarang. In taking samples, researchers used purposive sampling techniques. The instruments used in this research were observation, questionnaires and interviews. Based on the pre-test carried out, the results showed that students experienced anxiety at a very high level of 3.5%, whereas after being given classical guidance services which were carried out in two cycles, the results of the post-test were that students experienced a decrease in anxiety levels to 1.8% including in the low category.